Effective parameters in determining cross-linked dextran microsphere characteristics: screening by Plackett–Burman design-of-experiments. (26th March 2013) - Kenari, Hamed Salimi; Alinejad, Zeinab; Imani, Mohammad; Nodehi, Azizollah
Abstract : This study aims to screen the effective parameters in preparing cross-linked dextran microspheres (CDMs) to make them controllable for obtaining microspheres with tunable properties. Microspheres were prepared by chemical crosslinking of dextran dissolved in internal phase of an inverse emulsion system (W/O) using epichlorohydrin (ECH). A Plackett–Burman design-of-experiments was employed as the screening methodology to investigate the effects of the kinetics and process parameters, i.e. the mixing speed and emulsification time on the resulting microsphere characteristics. Crosslinking reaction temperature and concentrations of the emulsion constituents including dextran, ECH and sodium hydroxide were the studied kinetic parameters. Equilibrium swelling ratio, mean particle size and size distribution of the resulting CDMs were measured and statistically analysed. It was found that dextran concentration is the most influential parameter on the particle size and swelling ratio of the obtained CDMs. Increasing dextran concentration in the aqueous phase leads to a significant increase in the mean particle size and decrement in water uptake capacity of the resulting microspheres, respectively.